2014
DOI: 10.3389/fphys.2014.00171
|View full text |Cite
|
Sign up to set email alerts
|

A structural view of ligand-dependent activation in thermoTRP channels

Abstract: Transient Receptor Potential (TRP) proteins are a large family of ion channels, grouped into seven sub-families. Although great advances have been made regarding the activation and modulation of TRP channel activity, detailed molecular mechanisms governing TRP channel gating are still needed. Sensitive to electric, chemical, mechanical, and thermal cues, TRP channels are tightly associated with the detection and integration of sensory input, emerging as a model to study the polymodal activation of ion channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 120 publications
(172 reference statements)
1
52
0
Order By: Relevance
“…The mutant channel now elicited functional characteristics of mammalian channels, with evidently slower activation kinetics of the macroscopic current and the G-V curve shifted ;180 mV toward more positive potentials (V 0.5 = +148 mV; Figure 5D). This result highlights the important role of the TD helix in the regulation of channel gating and the fine-tuned modulation that occurs in this region (Brauchi et al, 2007;Gregorio-Teruel et al, 2014;Steinberg et al, 2014). Thus, all our observations are in reasonable agreement with architecture, voltage dependence, and the well-described regulatory role of the C-terminal domain in mammalian TRPM and TRPV channels (Clapham, 2009;Latorre et al, 2009).…”
Section: Cloning Heterologous Expression and Biophysical Characterisupporting
confidence: 78%
See 1 more Smart Citation
“…The mutant channel now elicited functional characteristics of mammalian channels, with evidently slower activation kinetics of the macroscopic current and the G-V curve shifted ;180 mV toward more positive potentials (V 0.5 = +148 mV; Figure 5D). This result highlights the important role of the TD helix in the regulation of channel gating and the fine-tuned modulation that occurs in this region (Brauchi et al, 2007;Gregorio-Teruel et al, 2014;Steinberg et al, 2014). Thus, all our observations are in reasonable agreement with architecture, voltage dependence, and the well-described regulatory role of the C-terminal domain in mammalian TRPM and TRPV channels (Clapham, 2009;Latorre et al, 2009).…”
Section: Cloning Heterologous Expression and Biophysical Characterisupporting
confidence: 78%
“…Because the TD helix has been proposed to be a negative allosteric modulator of TRP channel activation (Latorre et al, 2009;Gregorio-Teruel et al, 2014), we tested a subtle mutation within the conserved TRP-box sequence. The position Arg-759 is equivalent to Lys-698 in TRPV1, a residue that was recently suggested to be important for the regulation of the channel's gate (Steinberg et al, 2014). To test this directly, we replaced the naturally occurring arginine with the conserved lysine residue present in most mammalian channels.…”
Section: Cloning Heterologous Expression and Biophysical Characterimentioning
confidence: 99%
“…It has been reported that multiple tyrosine residues play distinct roles in ligand-activated channels, such as the GABAc receptor and 5-hydroxytryptamine receptor (25,26). Ligand binding sites in TRP channels were studied using sitedirected mutagenesis, chimeric analysis between different TRP channels, and structural data (27). The three-dimensional structure of TRPA1 was revealed by electron microscopy (28) in which TRPA1 was shown to form tetramer.…”
Section: Discussionmentioning
confidence: 99%
“…40 As discussed by Steinberg et al, PIP2 binding to TRP channels may favor reconfiguration of their structural determinants in order to promote channel activation. 41 Nonetheless, it is evident that, structurally, the regulation of TRPV4 activation by PIP2 seems to involve a different mechanism to that described for TRPV1, for example, since PIP2 binds to different regions in these channels.…”
mentioning
confidence: 97%
“…TRPV4 is a channel activated by temperatures that range from [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] C, by changes in osmotic pressure and by molecules of a lipid nature which are downstream of the activity of PLC, 39 among others. In this case, binding of PIP2 to the N-terminus of TRPV4 was shown to be important for activation of the channel by heat and hypotonic stimuli.…”
mentioning
confidence: 99%